Prevalence of mental disorders in adult populations from the Global South following exposure to natural hazards: a meta-analysis - A. Kip; S. Valencia; E. Glunz; S. R. Lowe; K.-P. Tam; N. Morina (Epidemiology and Psychiatric Sciences, 2024)
Abstract Aims Although natural hazards (e.g., tropical cyclones, earthquakes) disproportionately affect developing countries, most research on their mental health impact has been conducted in high-income countries. We aimed to summarize prevalences of mental disorders in Global South populations (classified according to the United Nations Human Development Index) affected by natural hazards.